Deciphering the role of granular activated carbon (GAC) in anammox: Effects on microbial succession and communication. (15th April 2023) - Gao, Mengjiao; Dang, Hongyu; Zou, Xin; Yu, Najiaowa; Guo, Hengbo; Yao, Yiduo; Liu, Yang
Highlights: GAC shortened lag phase by 45 days and enhanced NRR compared to a non-GAC reactor. GAC stimulated C12-HSL QS signal molecule secretion. GAC enriched Ca. Kuenenia and distinct anammox community over the non-GAC reactor. GAC enhanced AHL-dependent quorum sensing. Microbial cross-feeding supported anammox metabolism. Abstract: Anaerobic ammonium oxidation (anammox) offered an energy-efficient option for nitrogen removal from wastewater. Granular activated carbon (GAC) addition has been reported that improved biomass immobilization, but the role of GAC in anammox reactors has not been sufficiently revealed. In this study, it was observed that GAC addition in an upflow anaerobic sludge blanket (UASB) reactor led to the significantly shortened anammox enrichment time (shortened by 45 days) than the reactor without GAC addition. The nitrogen removal rate was 0.83 kg N/m 3 /day versus 0.76 kg N/m 3 /day in GAC and non-GAC reactors, respectively after 255 days' operation. Acyl-homoserine lactone (AHL) quorum sensing signal molecule C8-HSL had comparable concentrations in both anammox reactors, whereas the signal molecule C12-HSL was more pervasive in the reactor containing GAC than the reactor without GAC. Microbial analysis revealed distinct anammox development in both reactors, with Candidatus Brocadia predominant in the reactor that did not contain GAC, and Candidatus Kuenenia predominant in the reactor that contained GAC. Denitrification bacteria likely supported anammox metabolism in both reactors. The analyses of microbial functions suggested that AHL-dependent quorum sensing was enhanced with the addition of GAC, and that GAC possibly augmented the extracellular electron transfer (EET)-dependent anammox reaction. Graphical abstract: Image, graphical abstract